Effects of different surface modification and contents on municipal solid waste incineration fly ash/epoxy composites - Goh, C.K.; Valavan, S.E.; Low, T.K.; Tang, L.H. (Waste management (Elmsford), 2016)
[Display omitted] •Surface modified of 10–30% MSWI fly ash improved flexural and tensile modulus of composite.•Colloidal mesoporous silica enhanced bonding of MSWI fly ash and epoxy resin.•Epoxy matrix of the composite is able to immobilise toxic metals presence in MSWI fly ash. Incineration fly ash, a waste from municipal solid waste incineration plant can be used to replace conventional filler as reinforcing filler to enhance the mechanical strength of a composite. Surface modification was performed on the incineration fly ash before mixing into the soft polymer matrix so as to improve interfacial bond of the filler and epoxy resin. In this study, detailed characterisation of mechanical, morphological and leaching behaviours of municipal solid waste incineration (MSWI) fly ash infused composite has been carried out. Flexural and tensile test was conducted to determine the effect on mechanical properties of the composite by varying the concentration of incineration fly ash filler added into polymer matrix and surface modification of incineration fly ash filler using silane coupling agent and colloidal mesoporous silica (CMS). The results indicated that composite infused with incineration fly ash filler surface treated with CMS shown improvement on the tensile and flexural strengths. In addition, SEM images showed that surface modification of incineration fly ash with colloidal mesoporous silica enhanced the interfacial bonding with polymer resin which explained the improvement of mechanical strength. Leaching test showed result of toxic metals such as Pb, Zn, Fe, Cu, Cr, Cd and Rb immobilised in the polymer matrix of the composite. Hence, the use of MSWI fly ash as reinforcing filler in the composite appears green and sustainable because this approach is a promising opportunity to substitute valuable raw material with MSWI fly ash.